The Love of a Good Man? Romantic Relationships as a Source of Support or Hindrance for Female Ex-Offenders - Leverentz, Andrea M. (Journal of research in crime and delinquency, 2006)
This article explores the impact of romantic relationships on the reentry experiences of female ex-offenders. Although attachment to a prosocial spouse is an important social bond in the desistance of male offenders, male and female offenders have different offending and life experiences and are likely to draw romantic partners from very different groups. This article addresses this issue through an analysis of qualitative interviews with 49 female ex-offenders and their romantic partners. These women most often have relationships with recovering drug users and/or ex-offenders, not purely prosocial men or women. These relationships are dynamic and may be both destructive and conventionalizing at different points in time. Many women also consciously avoid romantic relationships, at least temporarily. These patterns of romantic relationships for female ex-offenders add to our understanding of the role of social bonds in desistance. This article emphasizes the need to look at relationships as processes rather than static events and to expand the definition of prosocial partners. [ABSTRACT FROM AUTHOR]